2012
DOI: 10.1074/jbc.m112.345702
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis Mutation R444L Causes Endoplasmic Reticulum Retention and Misprocessing of Vacuolar H+-ATPase a3 Subunit

Abstract: Background:The human V-ATPase a3 subunit mutation, R444L, causes infantile malignant osteopetrosis. Results: In mouse, the R444L equivalent, R445L, causes endoplasmic reticulum retention, misprocessing, and defective trafficking of a3 to the plasma membrane. Conclusion: Arginine 444/445 plays a critical role in mammalian a3 folding, or stability. Significance: R444L a3 infantile malignant osteopetrosis is a protein folding disease that may be amenable to protein rescue therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…It was recently demonstrated that glycosylation of residue R444 in V0a3, an osteoclast specific V0a isoform, is required for its proper delivery to lysosomes (Bhargava et al, 2012). To investigate the role of glycosylation on the V0a1 subunit, we generated an R447L mutant analogous to the R444L mutation in V0a3, using a C-terminal flag tagged V0a1 (V0a1-flag) that enabled the mutant to be differentiated from endogenous V0a1 subunit in murine neuroblastoma (N2a) cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that glycosylation of residue R444 in V0a3, an osteoclast specific V0a isoform, is required for its proper delivery to lysosomes (Bhargava et al, 2012). To investigate the role of glycosylation on the V0a1 subunit, we generated an R447L mutant analogous to the R444L mutation in V0a3, using a C-terminal flag tagged V0a1 (V0a1-flag) that enabled the mutant to be differentiated from endogenous V0a1 subunit in murine neuroblastoma (N2a) cells.…”
Section: Resultsmentioning
confidence: 99%
“…In less common cases, lysosomal dysfunction arises through mutations in genes encoding proteins that reside in another organelle but impact the function of a lysosomal constituent as their primary disease effect. Examples include osteopetrosis (Bhargava et al, 2012), Wolfram Syndrome (Gharanei et al, 2013), and PS1-FAD (Lee et al, 2010a; Lee et al, 2015), all of which are disorders where the mutated protein residing in the ER impairs the stability, delivery, or function of a lysosomal constituent. While most LSDs involve dysfunction of proteins that are ubiquitous in lysosomes throughout the body, it is remarkable that many LSDs have particularly devastating effects on the CNS.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
“…One of these mutations was shown to impair maturation and processing of V0a3 in osteoclasts. The mutated V0a3 is retained in the ER instead of being localized to lysosomes where it would normally be integrated as part of the v-ATPase (Bhargava et al, 2012). In addition to V0a3 being a component of the lysosomal v-ATPase, osteoclasts express the V0a3 isoform of the V0a subunit and use the v-ATPase to acidify extracellular compartments for bone reabsorption (Toyomura et al, 2003).…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
“…, the a subunit is misfolded, unglycosylated, retained in the ER, and ultimately subjected to proteolytic degradation (20). It was of interest, therefore, to determine whether the cutis laxa and dRTA mutations have similar impacts on a2 and a4 subunits, respectively, using methods for assessing N-glycosylation and stability that were previously described (25).…”
Section: R444lmentioning
confidence: 99%
“…For example, mutations affecting the function of a2 result in cutis laxa (wrinkled skin syndrome), where aberrant Golgi function results in glycosylation defects with consequent abnormal elastin processing that affects skin and internal organs (16)(17)(18). Mutations that affect a3 function result in inability of osteoclasts to resorb bone, causing autosomal malignant osteopetrosis that is characterized by dense, brittle bone (19,20). Loss of a4 function due to mutation results in distal renal tubular acidosis (dRTA) with occasional hearing loss (21,22) Here we focus on the effect of human mutations on a2 traffic to Golgi and a4 traffic to the plasma membrane based on their proposed in vivo locations and functions.…”
mentioning
confidence: 99%